2020
DOI: 10.1016/j.hroo.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery to aLleviate OCcurrence of Atrial Fibrillation Hospitalization—BLOC-AF

Abstract: Background Obesity is associated with a higher incidence of atrial fibrillation (AF). Weight reduction improves outcomes in patients known to have AF. Objective The purpose of this study was to compare the incidence of heart failure (HF) or first-time AF hospitalization in obese patients undergoing bariatric surgery (BAS) vs other abdominal surgeries. Methods A retrospective cohort study was conducted using linked hospital discharge records f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…39 Some of the benefit of exercise training may be due to weight loss, as weight loss is associated with improved AF symptoms and burden. 40 These results demonstrate that the increased AF incidence observed in endurance athletes does not extend to the more common population of individ-uals with AF, who are obese, with obstructive sleep apnea hypertension, and metabolic syndrome/diabetes. 7 Given the heterogeneous nature of the exercise interventions and the few studies that evaluated AF recurrence and burden, additional larger RCTs with ambulatory monitoring are needed to identify the optimal exercise strategy for AF.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…39 Some of the benefit of exercise training may be due to weight loss, as weight loss is associated with improved AF symptoms and burden. 40 These results demonstrate that the increased AF incidence observed in endurance athletes does not extend to the more common population of individ-uals with AF, who are obese, with obstructive sleep apnea hypertension, and metabolic syndrome/diabetes. 7 Given the heterogeneous nature of the exercise interventions and the few studies that evaluated AF recurrence and burden, additional larger RCTs with ambulatory monitoring are needed to identify the optimal exercise strategy for AF.…”
Section: Discussionmentioning
confidence: 72%
“…Cohort studies of risk factor modification with an exercise prescription have shown improved arrhythmia-free survival after AF ablation 39. Some of the benefit of exercise training may be due to weight loss, as weight loss is associated with improved AF symptoms and burden 40. These results demonstrate that the increased AF incidence observed in endurance athletes does not extend to the more common population of individuals with AF, who are obese, with obstructive sleep apnea hypertension, and metabolic syndrome/diabetes 7…”
Section: Discussionmentioning
confidence: 99%
“…The reason for exclusion of other trials was specified (lack of details, no controls, pre-existing AF, Figure 1 ). Ten studies [ 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] fulfilled the inclusion criteria ( Table 1 shows details of the 10 studies included in this meta-analysis). The protocol of the meta-analysis has been registered (Prospero, CRD42022374548).…”
Section: Methodsmentioning
confidence: 99%
“… ( A ) Forest plot of pooled hazard ratios of atrial fibrillation [ 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]; ( B ) funnel plots with 95% CI; ( C ) meta-regression analysis of effect as a function of age of BS patients (a) and of the whole cohorts (b). OR = Odds Ratio; 95% CI = confidence interval; SE, standard error.…”
Section: Figurementioning
confidence: 99%
“…Newer methods include gastric plication, single anastomosis duodeno-ileal bypass -SADI and ileal interposition. Endoscopic methods of obesity treatments are gastric balloon (due to the lack of maintenance of safety devices and the repair of end devices of this method, which ensure the performance of operations that are performed, or that are of high-quality BMI, as well as recorded operational inspections) [15][16][17][18] Bariatric surgery reduces obesity-related disorders that indirectly affect the development of AF. In patients undergoing bariatric surgery, the risk of either HF or AF was reduced by ∼29%.…”
Section: Bariatric Surgerymentioning
confidence: 99%